Developing self-regulated learning in accounting students: A guide for educators - Malan, Marelize; Els, Gideon; Karsten, Ilse (Journal of Management and Business Education, 2025)
Higher education educators need to equip students with self-regulated learning skills to keep up with ongoing global changes. Self-regulated learning is the ability of a student to set learning goals, monitor progress, adjust strategies, and control their learning process. There are different models proposed in the literature to develop and enhance the self-regulation process. The objective of this paper is to develop a practical programme based on self-regulated learning models for educators to incorporate into their existing curriculum, aiming to enhance students' self-regulated learning skills, particularly within an accounting curriculum. Using an action research methodology, the programme was developed through two action research cycles, with both quantitative and qualitative data collected and analysed. The findings indicate that the proposed programme, grounded in self-regulated learning models, helped students take control of their learning process by setting goals, reflecting on their progress, managing their learning environment, and staying motivated. The paper demonstrates how educators can integrate this programme into their curriculum, offering valuable strategies for fostering self-regulated learning, which is crucial for students' academic success and future professional development in a rapidly changing global environment.